Incidence of Sindbis Virus in Hospitalized Patients With Acute Fevers of Unknown Cause in South Africa, 2019–2020 - Meno, Kgothatso; Yah, Clarence; Mendes, Adriano; Venter, Marietjie (Frontiers in Microbiology, 2022)
Background Sindbis virus (SINV) is a mosquito-borne alphavirus that is widely distributed worldwide. Little is known about the febrile and neurological disease burden due to SINV in South Africa. Patients and Methods Clinical samples of patients with acute febrile disease of unknown cause (AFDUC) were collected through the African Network for Improved Diagnostics, Epidemiology and Management of Common Infectious Agents at three sentinel hospital surveillance sites in South Africa. In total, 639 patients were screened using a PCR-based macroarray that can simultaneously detect nucleic acids of 30 pathogens, including SINV, from January 2019 to December 2020. Serum samples were randomly selected from the arbovirus season (January–June) and also screened with a commercial indirect immunofluorescence assay for anti-SINV IgM. In addition, 31 paired cerebrospinal fluid (CSF) specimens from the same patients were screened for IgM. Micro-neutralization assays were performed on all IgM-positive samples. Results None of the specimens tested positive for SINV by molecular screening; however, 38/197 (19.0%) samples were positive for SINV-specific IgM. A total of 25/38 (65.8%) IgM-positive samples tested positive for SINV-neutralizing antibodies, giving an overall incidence of 12.7%. Furthermore, 2/31 (6.5%) CSF specimens tested positive for IgM but were negative for neutralizing antibodies. There was a higher incidence of SINV-positive cases in Mpumalanga (26.0%) than Gauteng province (15.0%). The most significant months for IgM-positive cases were April 2019 (OR = 2.9, p < 0.05), and May 2020 (OR = 7.7, p < 0.05). Conclusion SINV or a closely related virus contributed to 12.7% of AFDUC cases in hospitalized patients during the late summer and autumn months in South Africa and was significantly associated with arthralgia, meningitis, and headaches.